Drafting Laws for The Lifeless: A Legal Framework for Criminal Liability and Punishment for Artificial Intelligence - Wawan Fransisco (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
In this modern era, Artificial Intelligence (AI) has penetrated almost every aspect of life, offering tremendous benefits to humanity. However, like two sides of a coin, AI also presents serious risks, including its use in criminal act. For example, AI-powered lethal autonomous weapons can select targets and make killing decisions without human involvement. Similarly, autonomous cars can cause fatal accidents. A crucial question arises in these cases: Who should be held accountable? Is it the developer, the owner, the user, the supervisor, or even the AI itself? In criminal law, liability requires two main elements: actus reus (wrongful act) and mens rea (malicious intent). However, is it possible for AI to have malicious intent? Can AIs be treated as legal subjects worthy of punishment? This article critically examines the legal dilemma and offers three conceptual models to enable AI criminal liability. In addition, it analyses the possibility of imposing sanctions, such as imprisonment and fines, on non-human entities, as well as the relevance of theories of punishment in the context of AI. An analysis of the benefits and risks of punishing AI is also comprehensively outlined as an alternative to other solutions.